Theoretical study of the tuning role of β-methylthio or β-methylselenyl on the charge-transport properties of acenedithiophenes derivatives. Issue 15 (29th March 2023) - Li, Hui-Yuan; Qin, Gui-Ya; Lin, Pan-Pan; Sun, Xiao-Qi; Fan, Jian-Xun; Wang, Rui; Li, Hui; Zou, Lu-Yi; Guo, Jing-Fu; Ren, Ai-Min
Abstract : We investigate the reason why β-methylthio and β-methylselenyl substitution alter the molecular stacking in organic semiconductor crystals, in terms of the intermolecular interaction energy. Abstract : To date, the manipulation of intermolecular nonconjugation interactions in organic crystals is still a great challenge due to the complexity of weak intermolecular interactions. Here we designed molecules substituted by β-methylselenyl on naphtho[1, 2- b :5, 6- b ′]dithiophene and anthra[2, 3- b :6, 7- b ′]dithiophene, respectively (anti-β-MS-NDT, anti-β-MS-ADT), which together with anti-β-MS-BDT synthesized experimentally all exhibited 2D brickwork π-stacking. Moreover, their maximum molecular carrier mobilities reached 3.30 and 16.46 cm 2 V −1 s −1 . These results indicated that the substitution of β-methylselenyl could be a strategy to directionally adjust the parent herringbone stacking into 2D brickwork π-stacking. Hirshfeld surface analysis and symmetry-adapted perturbation theory (SAPT) were used to investigate the nonconjugated interactions in the pitched π-stacking formed by the β-methylthio-substituted acenedithiophene derivatives and the 2D brickwork π-stacking of the β-methylselenyl-substituted ones; wherein, the steric hindrance caused by the introduction of the substituents promoted Csp 2 –Csp 2 ⋯π interactions to replace Csp 2 –H⋯π to stabilize the face-to-face stacking. Moreover, by calculating the decomposition energy of the intermediate state model of the molecular stacking mode that may exist in the replacement conversion process, it was found that the energy of this intermediate state was larger than that of the actual ones, finally confirming the inevitability of the actual existence in this stacking. In addition, because of the reduction in intensity of the special vibration modes, it could be found that the β-methylselenyl substitution showed better phonon assistance than β-methylthio substitution in terms of dynamic disorder. This study is a further step toward fully understanding the relationship between intermolecular interactions and regulation of the molecular stacking.